2022
DOI: 10.1111/psyp.14119
|View full text |Cite
|
Sign up to set email alerts
|

Measuring human trace fear conditioning

Abstract: Trace fear conditioning is an important research paradigm to model aversive learning in biological or clinical scenarios, where predictors (conditioned stimuli, CS) and aversive outcomes (unconditioned stimuli, US) are separated in time. The optimal measurement of human trace fear conditioning, and in particular of memory retention after consolidation, is currently unclear. We conducted two identical experiments ( N 1 = 28, N 2 = 28) with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 52 publications
3
8
3
Order By: Relevance
“…Secondly, results from parallel methodological work and the current placebo group indicated that our pre-registered and exploratory analyses were unexpectedly underpowered. Effect size to measure trace fear memory retention was smaller in the present placebo group (Cohen's d = 0.31) than in two preceding experiments not involving drugs (Cohen's d = 0.44) (Wehrli et al, 2022).…”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“…Secondly, results from parallel methodological work and the current placebo group indicated that our pre-registered and exploratory analyses were unexpectedly underpowered. Effect size to measure trace fear memory retention was smaller in the present placebo group (Cohen's d = 0.31) than in two preceding experiments not involving drugs (Cohen's d = 0.44) (Wehrli et al, 2022).…”
Section: Discussioncontrasting
confidence: 83%
“…These results indicate successful learning and memory retention in our paradigm (see figure 3a, 4a, 3-1 and 4-1). As in our previous work (Wehrli et al, 2022), there was no evidence for a CS+/CS-difference in PSR in the recall test (see figure 4-1).…”
Section: Placebo Group Analysissupporting
confidence: 77%
See 3 more Smart Citations